Oridonin-Loaded Nanoparticles Inhibit Breast Cancer Progression Through Regulation of ROS-Related Nrf2 Signaling Pathway - Zhao, Yue; Xiao, Weiwei; Peng, Wanqing; Huang, Qinghua; Wu, Kunru; Evans, Colin E.; Liu, Xinguang; Jin, Hua (Frontiers in Bioengineering and Biotechnology, 2021)
Oridonin (ORI) has been shown to inhibit tumor cell growth and proliferation in vitro, while its optimum anti-tumor activity in vivo is limited due to the poor aqueous solubility and bioavailability. In this study, to improve the bioavailability, we developed a nanoparticle-based drug delivery system to facilitate delivery of ORI to breast tumor. ORI was encapsulated in biodegradable nanoparticles (NPs) based on poly-lactic-co-glycolic acid (PLGA) and polyethylene glycol (PEG) to form ORI NPs (ORI-NPs). The resulting ORI-NPs exhibited a mean particle diameter of 100 nm and displayed an efficient cellular uptake by human breast cancer MCF-7 cells. Compared to free ORI that showed no effects on tumor cell proliferation, the ORI-NPs showed significant cytotoxicity and delayed endothelial cell migration, tube formation and angiogenesis. Pharmacokinetics studies showed that ORI-NPs significantly increased the half-life of ORI in the blood circulation. In the nude mouse xenograft model, ORI-NPs markedly inhibited tumor growth and angiogenesis, while ORI did not show any inhibitory effects on the growth of tumor xenografts. The mechanism experiments showed that the antitumor activity of ORI-NPs against breast cancer might be through ROS related Nrf2/HO-1 signaling pathway. Together, these results demonstrated that ORI-loaded PEG-PLGA NPs enhanced bioactivity and bioavailability in vivo over ORI, indicating that ORI-NPs may represent a promisingly effective candidate against breast cancer.